Total L-carnitine and Insulin Resistance in Non-Obese and Obese Iraqi Women with Polycystic Ovary Syndrome - Shallal , Maad M.; Mahmood, Najmah M.; Hussein, Zina A. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Polycystic ovary syndrome (PCOS) is one of the most frequent endocrine illnesses affecting reproductive - age women. L-carnitine has important roles in oxidative stress, energy production and glucose metabolism. It affects insulin resistance as decreased plasma carnitine level has been well reported in type II diabetes mellitus. Hence, it means L-carnitine may reduce insulin resistance which is found in PCO disease.Objective: This study aims to measure the level of L-carnitine and insulin resistance in both obese and non- obese patients with PCOS.Methods: Sixty women within the reproductive age with PCOS (30 obese and 30 non- obese) were recruited from the Gynecology and Obstetrics Outpatient Clinic in Baghdad Teaching Hospital from June 2016 to June 2017. The data collected for each case included: Height, weight, waist circumference, blood pressure, obstetrical, medical, and medication history as well as ultrasound results. A physical examination was done to evaluate the clinical signs of hyperandrogenism. Biochemical measurements included fasting blood sugar, leutinizing hormone, follicular stimulating hormone, Testosterone, and lipid profile were measured together with total L-carnitine (using L-Carnitine Assay Kit Sigma-Aldrich Co.). Insulin resistance was diagnosed according to the National Cholesterol Education Program/Adult Treatment Panel III (NCEP/ATP III). PCOS is diagnosed according to the Rotterdam criteria.Results: This study revealed that insulin resistance (IR) was present in 51.7% of PCOS patients, which was higher in obese PCOS patients (73.3%) than in the non-obese (30%). Age of patients, serum cholesterol, LH, and FSH were not related to IR. High mean BMI, waist circumference, FBS, and triglyceride were significantly associated with IR (p < 0.05), while low serum HDL and L-Carnitine were associated with IR (p < 0.05). The mean serum total L-carnitine in this study was 34.03μmol/L. Obese women had lower carnitine levels than non-obese women and low serum L-Carnitine was associated with IR. Serum triglyceride, FBS, and testosterone were correlated negatively with serum L-carnitine (p < 0.05) and serum HDL correlated positively with serum L-carnitine (p-value = 0.001).Conclusions: The mean value of serum total L-carnitine among the non-obese PCOS women was higher than among the obese ones. Low serum L-carnitine is associated with insulin resistance